Investigating magneic properties of dot - Öztürk, Zeynep Reyhan. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
Magnetic insulators with perpendicular magnetic anisotropy enable low-power spin-orbit torque switching, high-frequency oscillation, and fast domain-wall motion [1]. Ferromagnetic insulators with PMA are key for studying skyrmions, magnetooptics, and memory/logic applications [2–4]. Yttrium iron garnet (YIG), with its perpendicular magnetization, revolutionizes current spintronics and magnonics. This work focuses on growing thin/ultrathin YIG films on Silicon substrates using Pulsed Laser Deposition (PLD) and explores the strain’s impact on magnetic anisotropy. We achieved perpendicular magnetic anisotropy without additional layers or doping materials. Additionally, we studied the magnetic properties of Permalloy (NiFe) thin films with dot/antidot arrays that have the ability to modify the magnetic behavior of magnetic thin films such as the magnetization reversal mechanism, magnetic domains, and control the magnetic anisotropy. The FMR technique determined the magnetization dynamics of the dot/antidot patterned NiFe thin films. The magnetization reversal of various shape, size, and thickness of dot/antidot array were investigated by a micromagnetic simulation, Mumax3 which solves the Landau-Lifshitz-Gilbert (LLG) equation. The remnant magnetization and coercive fields of the structures were extracted from the hysteresis loops. We discovered the excitation of spin-wave modes related to the shape effect from the FMR spectrum and found out different domain wall structures corresponding to different dot/antidot shapes from the simulations.
Keywords: Microwave devices.; Magnetic materials.